2020
DOI: 10.3389/fnhum.2020.571035
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological Comorbidities and Clinical Variables in Patients With Medication Overuse Headache

Abstract: The psychopathological profile of patients with medication overuse headache (MOH) appears to be particularly complex. To better define it, we evaluated their performance on a targeted psychological profile assessment. We designed a case-control study comparing MOH patients and matched healthy controls (HC). Headache frequency, drug consumption, HIT-6, and MIDAS scores were recorded. All participants filled in the following questionnaires: Beck Depression Inventory-II Edition (BDI-2), trait subtest of State-Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…However, the MOH group reported mild to moderate depression symptoms. Our results confirm the findings from previous studies, investigating the behavioral and psychopathological profile of patients with MOH (1,27). Regarding the dissociative aspects, in our study, there were no differences among the three groups, even if few studies demonstrated that dissociative symptoms are more frequent in patients with migraine and, in particular, in chronic forms of migraine (28).…”
Section: Discussionsupporting
confidence: 92%
“…However, the MOH group reported mild to moderate depression symptoms. Our results confirm the findings from previous studies, investigating the behavioral and psychopathological profile of patients with MOH (1,27). Regarding the dissociative aspects, in our study, there were no differences among the three groups, even if few studies demonstrated that dissociative symptoms are more frequent in patients with migraine and, in particular, in chronic forms of migraine (28).…”
Section: Discussionsupporting
confidence: 92%
“…18,21,22 Our data have this trend, although there was no significant difference. On the other hand, although psychiatric comorbidities such as anxiety, depression, and others, plus altered hormone levels associated with mood swings in women over 40 years of age 7,23 , could lead to CDH and MOH, we found no significant differences for MOH in this subgroup. Shand et al 11 reported that the overused drugs that led to the development of MOH in Argentina and Chile were combined ergotamine (70%) and NSAIDs (33.8%).…”
Section: Discussioncontrasting
confidence: 79%
“…Several studies have determined associations with polymorphic variants related to the susceptibility of conversion to MOH 6 , psychopathological comorbidities 7 , within these, post-traumatic stress events 8 , depression, anxiety and insomnia 9 , and other sociodemographic factors, such as low education, place of residence, limited medical contact and type of medical care received in the development of MOH. [10][11][12][13] Factors that, in addition to transforming EM and ETTH into CM and CTTH [7][8][9]14,15 , induce patients to seek different types of medical attention and to overuse medication in an effort to obtain relief from their pain. [16][17][18][19] There is no clear evidence regarding the association of MOH with the type of medical care received.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Increasing headache frequency was associated with risk of occurrence of anxiety, depression, and insomnia, 25 and higher migraine frequency was correlated with greater symptom scores of anxiety and depression. 26 MOH patients showed a high rate of depression and anxiety, which could negatively affect their headache attack, 27 and depression and anxiety were found to be negative predictors in terms of treatment response in chronic migraine patients with or without medication-overuse. [28][29][30] Moreover, lowered depression scores predicted a positive outcome of MOH detoxification.…”
Section: Discussionmentioning
confidence: 95%